2010
DOI: 10.1128/jcm.00967-10
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-Negative Staphylococcal Skin Carriage among Neonatal Intensive Care Unit Personnel: from Population to Infection

Abstract: Coagulase-negative staphylococci (CoNS) are a major cause of sepsis in neonatal intensive care units (NICU) worldwide. Infecting strains of these commensal bacteria may originate from NICU personnel. Therefore, we studied the characteristics of CoNS isolates from NICU personnel and compared them to those of isolates from the general population and from sepsis patients. Furthermore, we studied the epidemiological effect on CoNS carriage of NICU personnel after a period of absence. In our study, we isolated CoNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Furthermore, others have proposed that hospitalization constitutes the most important factor for the accumulation of a hospital flora of CoNS [4]. In this aspect the skin flora of hospital personnel might be an important cause of cross-contamination of CoNS, as has been demonstrated in neonatal intensive care units [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, others have proposed that hospitalization constitutes the most important factor for the accumulation of a hospital flora of CoNS [4]. In this aspect the skin flora of hospital personnel might be an important cause of cross-contamination of CoNS, as has been demonstrated in neonatal intensive care units [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream isolates were frequently antibiotic resistant, similar to CoNS isolates from NICU personnel and from NICU sites (1,2). Previously, it was shown that the majority of CoNS causing sepsis among neonates can be found on the hands of NICU personnel (1). Since the incidence of antibiotic-resistant CoNS in the nonmedical population is low, it is generally assumed that neonates become colonized with antibiotic-sensitive CoNS after birth.…”
mentioning
confidence: 80%
“…This could be achieved through strict antiseptic measures for environment, staff, equipment, and minimizing invasive procedures [13]. These perfect control measures require proper epidemiological studies and tracing of infection [14]. The principal method of diagnosing sepsis is the isolation of causative organisms from blood cultures and antimicrobial susceptibility testing [15,16].…”
Section: Introductionmentioning
confidence: 99%